Soybean yield and yield components affected by the mycorrhiza and bradyrhizobium at different rates of starter nitrogen fertilizer - Aboutalebian, Mohammad Ali; Malmir, Masoumeh (Semina: Ciências Agrárias, 2017)
In order to study interaction between mycorrhiza and bradyrhizobium on yield of soybean under different amounts of starter nitrogen fertilizer, a field experiment was conducted at the agricultural research station, Bu-Ali Sina University in 2015 growing season. A factorial experiment based on randomized complete block design was arranged with three replications. Experiment factors covering three levels of starter nitrogen of 0, 30 and 60 kg ha-1, bradyrhizobiumin two level of inoculated and non-inoculated and mycorrhiza including application and non-application levels. Results indicated that plant height, number of leaves per plant, yield and yield components and biological yield and mycorrhizal symbiosis percent affected by interaction of studied factors significantly. Maximum number of pod per plant achieved from combination of 30 kg Nitrogen and bradyrhizobium. Also both bio-fertilizer was able to increase number of pod per plant. Maximum 1000 seed weight obtained from inoculation of plants with bradyrhizobium and mycorrhiza simultaneously with no nitrogen utilization. Application of 60 kg ha-1 nitrogen caused to decreased mycorrhizal symbiosis about 20.22 percent in comparison with no use of starter fertilizer. Application bradyrhizobium and mycorrhiza under the application of 30 kg ha-1 nitrogen, produced the highest grain yield (511.67 g m-2) and biological yield (1223.16 g m-2).